Pengembangan Game Survival Horor Unity 3D dengan Menerapkan AI pada NPC - Anang Habibi; Muhammad Ibnu Athoillah (Pusat Riset dan Inovasi Nasional, 2025)
The games industry in Indonesia continues to grow, but the contribution to game development is still low. This research aims to design a Survival Horror game that prioritizes an immersive gaming experience with elements of strategy, action and resource management. Inspired by Resident Evil and Silent Hill, this game utilizes a tense atmosphere and fear based on psychological studies, as explained by Norton & Gino (2014). With a focus on strategy and suspense, it is hoped that this game can provide an immersive gaming experience and contribute to the development of the local gaming industry.